2002
DOI: 10.1152/ajpendo.00038.2001
|View full text |Cite
|
Sign up to set email alerts
|

Function-specific calcium stores selectively regulate growth hormone secretion, storage, and mRNA level

Abstract: Ca+ stores may regulate multiple components of the secretory pathway. We examined the roles of biochemically independent intracellular Ca2+stores on acute and long-term growth hormone (GH) release, storage, and mRNA levels in goldfish somatotropes. Thapsigargin-evoked intracellular Ca2+ concentration ([Ca2+]i) signal amplitude was similar to the Ca2+-mobilizing agonist gonadotropin-releasing hormone, but thapsigargin (2 μM) did not acutely increase GH release, suggesting uncoupling between [Ca2+]i and exocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In the present study, the acute inhibitory GTH‐II release response is specific to Tg‐sensitive Ca 2+ stores, since it is not mimicked by other treatments that affect goldfish gonadotrope Ca 2+ stores (Ry, cyclopiazonic acid) (22, 23). In addition, the growth hormone release response measured under identical conditions is not inhibited by Tg (47, 48), suggesting cell specificity. To our knowledge, this is the first demonstration of an intracellular Ca 2+ store that specifically blocks basal hormone release when perturbed, without affecting agonist‐evoked exocytosis.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the acute inhibitory GTH‐II release response is specific to Tg‐sensitive Ca 2+ stores, since it is not mimicked by other treatments that affect goldfish gonadotrope Ca 2+ stores (Ry, cyclopiazonic acid) (22, 23). In addition, the growth hormone release response measured under identical conditions is not inhibited by Tg (47, 48), suggesting cell specificity. To our knowledge, this is the first demonstration of an intracellular Ca 2+ store that specifically blocks basal hormone release when perturbed, without affecting agonist‐evoked exocytosis.…”
Section: Discussionmentioning
confidence: 86%
“…Our results indicate that conventional and novel PKCs are not likely to be involved in GnRH-stimulated GH gene expression, suggesting that the signal transduction pathways mediating GnRH effects on GH gene expression are different from those regulating GH secretion in the goldfish pituitary. Indeed, previous studies in goldfish examining the regulation of GH secretion, storage, and gene expression by multiple intracellular Ca 2ϩ stores appear to support the hypothesis that secretion and gene expression can be independently controlled by function-specific signaling (26).…”
Section: Erk Mediates Gnrh-induced Gh Gene Expressionmentioning
confidence: 82%
“…Additionally, results from our previous investigations have indicated that gGnIH is also able to uncouple lhb mRNA expression and LH secretion . Post-receptor signaling mechanisms mediating differential actions of gGnIH on GH release and gene expression remain to be studied in the future, but differential use of pharmacologically distinct intracellular Ca 2C pools, protein kinase C, and ERK have been indicated to be factors enabling selective modulation of GH secretion and synthesis in goldfish (Johnson et al 2002.…”
Section: Steady-state Gh Mrna Expressionmentioning
confidence: 99%